Human Dimensions of Climate Change in Arid and Semi-arid Environments: A Case Study of Post-Soviet Central Asia - Lioubimtseva, Elena (Annals of Arid Zone, 2016)
Arid and semi-arid regions are expected to undergo significant environmental changes caused by the global climate change. Social, political and economic factors and processes, such as globalization, institutional and land-use changes, are likely to he determinant factors of human vulnerability and adaptations to impacts of climate change. This paper explores human dimensions of climate and environmental changes in arid and semi-arid zones of the Central Asian countries of the former USSR. Political, economic, and institutional changes in this region during the past decades have affected its sensitivity and adaptive capacity to climate change and climate variability in many ways. Various non-climatic factors, such as land-use changes, agricultural and economy-wide reforms, crisis of the national health care systems, forced migrations of the population, the general economic decline, and increase of poverty and inequality currently overwhelm the impacts of the global climate change. The same factors, however, are likely to exacerbate the projected impacts of climate change, such as the increasing climate aridity and variability, projected by the climate change scenarios. Key words: Human dimensions of climate change, Central Asia, arid environments, adaptations